Determinant Factors of Purchasing Intention Toward Electric Vehicles in Indonesia - Fahmi Setiadi; Nur Chayati (Riset Akuntansi dan Keuangan Indonesia, 2024)
This study aims to examine factors that affect the intention to buy an electric vehicle from the perspectives of the theory of planned behaviour, norm activation model, and frugality. The study's results reveal that attitudes, subjective norms, perceived behavioural control, personal norms, and frugality directly influence the intention to purchase an electric vehicle. Additionally, the perception of incentives, ascription of responsibility, and awareness of consequences also indirectly influence the intention to buy an electric vehicle. The study's findings suggest that both the government and entrepreneurs must play a significant role in hastening the transition from fossil fuel vehicles to electric vehicles. The government can implement both fiscal and non-fiscal policies. Specifically, it can provide fiscal incentives to encourage the purchase of electric vehicles and expedite the development of public electric vehicle charging station infrastructure, making it easier for consumers to charge their cars. Automotive entrepreneurs can contribute by promoting safe, comfortable, and affordable electric vehicles, thereby increasing consumer confidence in purchasing them. Products of electric vehicles are crucial in convincing consumers that they provide superior environmental solutions, as they prioritize advancing sustainability goals in the environmental sector rather than generating new environmental issues.